22 January, 16:31

# Need to solve this problem in steps 5 (2x+6) = -4 (-5-2x) + 3x

0
1. 22 January, 17:49
0
Simplifying

5 (2x + 6) = - 4 (-5 + - 2x) + 3x

Reorder the terms:

5 (6 + 2x) = - 4 (-5 + - 2x) + 3x

(6 * 5 + 2x * 5) = - 4 (-5 + - 2x) + 3x

(30 + 10x) = - 4 (-5 + - 2x) + 3x

30 + 10x = (-5 * - 4 + - 2x * - 4) + 3x

30 + 10x = (20 + 8x) + 3x

Combine like terms: 8x + 3x = 11x

30 + 10x = 20 + 11x

Solving

30 + 10x = 20 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.

30 + 10x + - 11x = 20 + 11x + - 11x

Combine like terms: 10x + - 11x = - 1x

30 + - 1x = 20 + 11x + - 11x

Combine like terms: 11x + - 11x = 0

30 + - 1x = 20 + 0

30 + - 1x = 20

Add '-30' to each side of the equation.

30 + - 30 + - 1x = 20 + - 30

Combine like terms: 30 + - 30 = 0

0 + - 1x = 20 + - 30

-1x = 20 + - 30

Combine like terms: 20 + - 30 = - 10

-1x = - 10

Divide each side by '-1'.

x = 10

Simplifying

x = 10